(untitled) (Research, Society and Development, 2022)
Objective: To know the nursing scientific production about the assistance of nurses to people with uterus in abortion situations, within a Brazilian scenario that hinders the autonomy of freedom of choice. Methodology: This is an integrative review with a survey of articles in the Scielo, BDENF and LILACS databases, from 2016 to 2021. Data collection occurred from April four to May ten, 2022 with the use of Descriptors in Health Sciences: "Nursing", "Nursing Care", "Abortion" and "Women’s Health". To search for the articles, the health descriptors were used with the Boolean operators: AND and/or OR. A total of 1,491 articles were found, of which 10 were selected according to eligibility for analysis. Results: Ten articles were selected for analysis and construction of this review. Two categories of discussion were originated: Social determinants and critical-reflexive training: repercussions in nursing care to women in abortion situation; Nursing care protocols to women in abortion situation. Conclusion: It is clear that the approach of nursing professionals is crucial for an integral and resolutive assistance to women in abortion situation.